Heliconia psittacorum: influência de fitoestimulantes no controle de manchas foliares e na qualidade de flores pós-colheita - Sardinha, Diogo Herison Silva (2018)
Obstructions to the production of heliconia are foliar diseases that can reduce photosynthesis, damage as broccoli and become unfeasible as flowers for commercialization. The use of phytostimulants can reduce leaf spot and influence the quality of post-harvest flowers. The objective of this work was to identify resistance forms in H. psittacorum cv. Golden Torch and positively influence the post-harvest of this species. Agro-Mos® phytostimulants (10 ml L-1), Bion® (0.5 g L-1), Quartz® (40 ml L-1), K - Fosfitotal® (3 g L-1) and Ca - Fosfitotal® (3 g L-1) was the auxiliary commissioner of costal spraying and each plot was protected during an application that eliminated the drift of the products. The induction was evaluated during the experimental cultivation with the quantification of the growth rate of the fungal complex, the photosynthetic of the plants and the collection of vegetal material for the enzymatic analysis of the enzyme peroxidase, polyphenoloxidase, β-1,3 gluconase. Post-harvest color was measured on flowers of H. psittacorum cv. Golden Torch. At the moment of the analysis, the visual effects, fresh mass loss, electrolyte extravasation, lipid peroxidation, besides the quantification of soluble carbohydrates and enzymes peroxidase, polyphenoloxidase, superoxide dismutase and total soluble phenolic compounds. The results indicate that Bion® phytostimulants and applied phosphites reduced fungal complex severity, increased peroxidase, polyphenoloxidase, β-1,3 gluconase activity, and did not promote changes in the net photosynthesis rate of plants. The value found for β> 1, which is visual visual of the severity of the fungal complex, is a good visual indicator of the effect of phytopathogens on the photosynthetic rate of the host. The quality of the vitamins demonstrated is positive, preserving the quality of the plants harvested. The parameters were the phosphites, especially K - Fosfitotal ®, obtained the best notes for the visual aspect, revealed the extravasation of electrolytes and lower lipid peroxidation. The results of this work are concrete answers to the producers of the sector, on the alternatives of management of the diseases associated with the cultivation of heliconia.